2017
DOI: 10.1017/s0007114517003026
|View full text |Cite
|
Sign up to set email alerts
|

Time-series responses of swine plasma metabolites to ingestion of diets containingmyo-inositol or phytase

Abstract: The effect of the ingestion of diets containing either myo-inositol or exogenous phytase on plasma metabolites was examined using 29 kg barrows. The diets were: control (maize, soya, rapeseed, rice bran), control plus 2 g/kg myo-inositol, control plus 1000 phytase units (FYT)/kg or 3000 FYT/kg exogenous phytase. Pigs were housed in a PigTurn device and blood was collected, from jugular catheters, via an automated system at −30, (30 min before feeding), 0,15, 30, 45, 60, 90, 120, 150, 180, 240, 300 and 360 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…In addition, recent studies have reported a dose-dependent increase in phytate disappearance and myo-inositol concentrations in intestinal digesta of piglets with phytase [14,15,55,56]. Free myo-inositol is absorbed and can be detected in both portal and peripheral blood of pigs [15,52,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have reported a dose-dependent increase in phytate disappearance and myo-inositol concentrations in intestinal digesta of piglets with phytase [14,15,55,56]. Free myo-inositol is absorbed and can be detected in both portal and peripheral blood of pigs [15,52,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…According to Cowieson et al [17], diets that do not provide sufficient macro- and micro-nutrients (due to formulation or high levels of enzyme matrix) can prevent the pathways stimulated by myo-inositol from improving FCR by increasing protein accumulation and downregulating gluconeogenesis. Cowieson et al [15] and Schmeisser et al [32] indicated a positive effect of phytase on the concentration of myo-inositol, whose action mimics insulin, with similar effects on GLUT 4 when blood glucose concentration increases, which is involved in aspects related to gluconeogenesis and improves digestibility, weight gain, and feed conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Gonçalves et al [13], however, observed that the effects in finishing pigs are variable and appear to be more evident if the concentrations of digestible phosphorus and other nutrients are marginal in the diet. The benefits of this inclusion pattern are related not only to animal performance, but also to health, well-being, and, possibly, to meat quality [14], the latter being determined by the significant increase in the plasma levels of myo-inositol [15]. Besides that, the levels of inorganic phosphorus in animal diets can be decreased by using phytase, thus reducing phosphorus excretion to the environment [16].…”
Section: Introductionmentioning
confidence: 99%
“…Others (Guggenbuhl et al 2016;Laird et al 2018) have also found increased plasma inositol concentrations with increased dietary phytase application. A study done by Cowieson et al (2017) reported an immediate increase of plasma myo-inositol concentration after oral ingestion of myo-inositol, and 3000 FTU phytase /kg feed significantly increased plasma myo-inositol 6 h after feed intake. Therefore, the increased myo-inositol concentration in Downloaded from https://academic.oup.com/jas/advance-article-abstract/doi/10.1093/jas/skz234/5530987 by University of East Anglia user on 17 July 2019 A c c e p t e d M a n u s c r i p t the fed status at 2000 FTU/kg was likely due to the released myo-inositol by phytase.…”
Section: Inositol Phosphatesmentioning
confidence: 95%